COMPARATIVE ANALYSIS OF WORK LIFE BALANCE AND WORKING ENVIRONMENT BETWEEN MALE AND FEMALE EMPLOYEES IN PT BANK TABUNGAN NEGARA (PERSERO) TBK MANADO - Sambouw, Pamela Felita; Saerang, David P.E; Rumokoy, Farlane S. (Universitas Sam Ratulangi, 2017)
Abstract: Employees are the most important part of a company, especially in PT Bank Tabungan Negara (Persero)Tbk Manado with a good performance of employee it can increase the companyâ€™s values. With that condition Researcher want to help PT Bank Tabungan Negara Manado to to see is there any significant different in Work Life Balance and Working Environment between Male and Female employees. The researcher analyzes data based on primary data and secondary data by using SPSS software while, primary data is collected by distributing 100 questionnaires to 50 male and 50 female employee of PT Bank Tabungan Negara (Persero) Tbk. Secondary data is collected by reading various books, journal and browsing the internet. The researcher uses Independent Sample T-test. By using Independent sample T-test the result shows that there is no significant difference between Male and Female Customer in Work Life Balance and Working Environment. Based on the results, the data is normally distributed and homogenous. The researcher recommends for PT Bank Tabungan Negara (Persero) Tbk Manado no need to make a different between male and female employee in Work Life Balance and Work Environment.Â Keywords: work life balance, working environment, independent sample t-test, gender, banking sector.